(untitled) - Raymond A. Noe (Boston, Mass., 2004)
Fundamentals of Human Resource Management, by Noe, Hollenbeck, Gerhart and Wright is specifically written to provide a brief introduction to human resource management. While it doesn't cover the depths of human resource management theory, the book is rich with examples and engages students through application. This first edition takes on a different approach than the hardback text by the same team. Instead of a higher level of theory that's geared towards the HRM professional, this book focuses on the uses of human resources for the general population. Issues such as strategy are reduced to give a greater focus on how human resources is used in the every day work environment.
Keywords: Personnel management,Quản trị nhân sự